Influence of Assembly Errors and Tooth Surface Modification on Transmission Errors of Curvilinear Cylindrical Gears - Zhang Xuegang; Xie Yongchun; Wang Pengfei (Jixie chuandong)
Tooth surface equations of a curvilinear cylindrical gear with parabolic modification are derived based on the gear meshing theory. The solving method of the initial contact position of the gear finite element model is studied, a finite element model of the gear pair is established using the parameterized finite element technology, and the loaded transmission error is extracted from the finite element analysis results. With more than 20 sets of calculation examples, the effects of assembly errors, modification amount, curvature radius of the cutter, and offset of modification curve on loaded transmission errors are studied, respectively. The research results show that, assembly errors can reduce the fluctuation range of loaded transmission errors; larger modification amount can reduce the fluctuation range of loaded transmission errors; larger curvature radius of the cutter can reduce the value of loaded transmission errors and its fluctuation range; the offset of the modification curve has slight effect on loaded transmission errors. In summary, the use of a larger curvature radius of the cutter can be used to machine curvilinear cylindrical gears with better transmission performance.